Ecological Consciousness and Interconnectedness in John Steinbeck’s The Red Pony: An Ecocritical Study - Dhungel, Bharat (Journal of Durgalaxmi, 2025)
This research paper examines ecological consciousness in The Red Pony by John Steinbeck from an environmental perspective. It argues that the novel highlights the deep interconnection among human beings, the land, and animals through the experiences of the major characters, Jody Tiflin and Billy Buck. Their actions show how humans depend on land and animals for survival, how animals rely on humans and nature, and how nature itself gains meaning through its relationship with living beings, creating a harmonious and mutually supportive system necessary for coexistence. To analyze this relationship, the study adopts an ecological reading of the primary text and draws on major ecocritical theorists such as Aldo Leopold, Peter Singer, Lawrence Buell, and Paul Taylor, whose ideas help frame the novel’s environmental insights. The findings reveal that The Red Pony is rich in depictions of interdependence among humans, land, and animals, and the study concludes that Steinbeck successfully portrays ecological awareness by emphasizing that the survival and significance of each element of the natural world depend on their interconnected roles.